1984
DOI: 10.1002/1097-0142(19841001)54:7<1300::aid-cncr2820540712>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of chest radiography, computed tomography, and gallium scanning to metastasis of lung carcinoma

Abstract: To determine the efficacy of radiologic techniques in preoperative staging of the mediastinum for lung carcinoma, the authors studied 45 patients with chest films supplemented with oblique views, esophagrams, gallium scans, and computed tomograms (CT). They interpreted the studies and correlated surgical findings using a modified classification of lymph node regions. The mediastinum was positive on chest films in 14 of the 21 cases with pathologically proved mediastinal metastases (33% false‐negative). Gallium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…There are many explanations for the fact that more nodules and nodules of smaller sizes are detected using CT compared with thoracic radiographs. CT provides high‐resolution cross‐sectional images with minimal anatomic superimposition and superior contrast resolution 15,27,28 . In addition, standardized breath‐hold techniques appear to result in better and more consistent lung inflation that can improve nodule detection, particularly near aerated lung to soft‐tissue interfaces, such as the thoracic wall and diaphragmatic surfaces 17 .…”
Section: Discussionmentioning
confidence: 99%
“…There are many explanations for the fact that more nodules and nodules of smaller sizes are detected using CT compared with thoracic radiographs. CT provides high‐resolution cross‐sectional images with minimal anatomic superimposition and superior contrast resolution 15,27,28 . In addition, standardized breath‐hold techniques appear to result in better and more consistent lung inflation that can improve nodule detection, particularly near aerated lung to soft‐tissue interfaces, such as the thoracic wall and diaphragmatic surfaces 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Helical CT has previously been shown to be more sensitive than thoracic radiography for detection of pulmonary nodules in people. [1][2][3][4][5][6][7][8][9] Specifically, 1 study using helical CT to detect stage I pulmonary masses found that 73% of the affected patients had unremarkable thoracic radiographs, 9 and a 2nd study revealed that more nodules were detected using CT as compared with thoracic radiographs in 66% of the patients. 2 Even considering these findings in man, the degree to which helical CT surpassed thoracic radiographs for nodule detection and for the size threshold of detection in the current study was surprising.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specificity of CT for detecting pulmonary metastatic nodules can be lower than that of thoracic radiography because more small, nonneoplastic, and clinically insignificant nodules are likely to be identified. [8][9][10][11] Systematic studies comparing thoracic radiographic and CT techniques in veterinary patients with suspected pulmonary metastatic disease have, to our knowledge, not been reported. A study that directly compared the 2 techniques in a canine model of human disease found that CT was more sensitive than thoracic radiography for detecting pulmonary infarcts.…”
mentioning
confidence: 99%
“…Many studies have evaluated the global accuracy of CT in the staging of mediastinal nodal status in lung cancer [14][15][16][17][18][19][20][21][22][23]. Some of these studies have reported a high sensitivity, ranging 88-94% [14,15], values that are equivalent to the sensitivity obtained by mediastinoscopy [6,24,25].…”
Section: Discussionmentioning
confidence: 99%